Source Language and Culture Interference in Translation - Irina PUȘNEI, Dr. (ACROSS, 2023)
The translation is a process that goes beyond linguistic transformations and demands cross-cultural awareness. However, mistakes resulting from apparently similar linguistic structures in the source and target language as well as narrow cultural views can compromise the quality of the translated text. Therefore, the target audience may lose the thread of the text line or be completely misled. The goal of this paper is to discuss the concepts of the first language and cultural interference in the translation process as well as to bring forward some examples of frequent loan translations resulting from this phenomenon. Attempts to translate culture-specific patterns will be illustrated and the applied translation strategies analysis will confirm or refute their efficiency in bringing the source culture closer to the target audience.